Dynamics of snow park jump landings: A pilot study examining impact loads for elite athletes - Scher, I.; Stepan, L.; Campbell, J.; Bower, G.; Wilkens, K.; Gunnarson, C.; Hackett, T. (Science and Skiing VII, 2018)
Slopestyle is an event where a snowboarder performs tricks on a series of rails and jumps. Slopestyle competitions have become more popular with events such as the X-Games, Dew Tour, and Air and Style. Slopestyle was introduced as an Olympic event at the 2014 Winter Games in Sochi, Russia. While this event has soared in popularity, slopestyle had one of the highest injury rates per athlete in the Winter Olympics and FIS competitions from 2014 through 2015 (Soligard, 2015; Steenstrup, 2015). Previous scientific studies indicate that jumping features have higher injury rates than non-jumping features for recreational jumpers (and possibly for elite athletes) (Russell, 2013). The literature shows that recreational and elite athletes have different injury patterns (Wijdicks, 2014). Recreational snow park jumpers most often sustain upper-extremity injuries, while knee injuries are the most prevalent injury among elite slopestyle athletes and often cause athletes to miss four weeks or more of training and competition (Wijdicks, 2014; Soligard, 2015; Steenstrup, 2015). Ascertaining the jumper kinematics and loads produced during jumping could provide guidance for best practices and interventions to reduce the likelihood of injury. One research team (McAlpine, 2010) studied the loads generated and ankle mechanics when landing a jump using novel sensors. In their testing, subjects performed generally straight air maneuvers on non-competition jumps at both indoor and outdoor facilities. Though the number of jumpers was limited and they did not measure full-body kinematics, their data represented the best available information about the loads produced during recreational snowpark jumps. Unfortunately, these data do not provide enough information to assess landings on larger jumps by elite athletes performing complex maneuvers; the kinematics and loads produced by elite snowboarders while using competition-sized, tabletop features in snow parks has not been investigated. In this study, we measured the loads and body kinematics of elite snowboarders while landing on competition-sized jumps, similar to those found in slopestyle and big-air competitions, to • assess whether or not the equipment and methodology would be appropriate for use in a more complete, long-term study; • examine center-of-mass motion during typical landings; • investigate the loads at landing applied to the jumper through the snowboard bindings and at the center of mass; and • determine if equivalent fall height (a metric related to the landing velocity component into the snow surface) is related to the loads produced at the snowboard bindings.